THE HEROES’ JOURNEY: AN ARCHETYPAL ANALYSIS OF HANSEL AND GRETEL - altabaa, Homam; Nor Ainun Barieah Binti Zahari (Elite : English and Literature Journal, 2022)
There are numerous fairy tales in the European tradition, and especially in the Grimms’ collection, that employ numerous archetypal themes, characters and motifs. This is true of the popular story, Hansel and Gretel. The examination of archetypes can be a laborious task given their rich psychological and cultural significance and their widespread use among seemingly distinct civilizations and genres. Accordingly, this study analyses the use of archetypes in the Grimms’ collection - through the example of Hansel and Gretel - to explore their full significance as these archetypes could potentially be a reason behind the enduring popularity of this story and the collection in general. The methodology of this study is based on the archetypal stages of the hero’s journey or quest as elaborated by Joseph Campbell in his seminal work, The Hero with a Thousand Faces. This study has concluded that Hansel and Gretel skilfully employ numerous archetypal elements such as the evil women, order versus chaos, thresholds and helpers, and the trickster and the witch within the archetypal framework of a hero's journey to allow its protagonists to achieve psychological and moral maturity and material rewards. Through its few pages, Hansel and Gretel offers readers rich moral lessons about courage, regression, shrewdness, loyalty, evil, compassion and destiny through the use of the archetypal journey and its various elements. Keywords: Archetypes, fairytales, Hansel and Gretel, hero’s journey